IMPROVEMENT OF GROWTH, PHYSIOLOGICAL AND BIOCHEMICAL TRAITS OF SUNFLOWER BY IAA AND BAP UNDER SALINITY STRESS in vitro - Safa H. Kh.; S. I. Neamah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was established to investigate the ability of the sunflower callus plant (Helianthus annuus L.) to tolerate salinity stress for two levels of NaCl (0 and 80 mM), three concentrations of IAA (0, 1.0, and 2.0 mg l-1), and BAP (0, 1.0, and 2.0 mg l-1) in lab conditions. Calli cultures were induced from the cotyledon of H. annuus L. cultured in an appropriate combination of growth regulators 2,4-D and kintein. The salinity results exhibited negative effects in most of the study indications, which can be revealed by a significant increase in sodium content (Na+), hydrogen peroxide (H2O2) and malondialdehde content (MDA). While, the decrease in the study indications such as fresh weight (FW), dry weights (DW), relative water content (RWC), potassium content (K+), sodium/ potassium ratio (Na+/K+), superoxide dismutase (SOD), and catalase (CAT) enzymes activity. The experiment revealed a positive effect for the exogenous growth regulators IAA and BAP in reducing the harmful effects of salinity stress on calli cultures. The nominated regulators succeeded in reducing the harmful effects of salinity stress, where the FW, DW, RFW, browning density (BI), RWC, K+, Na+/K+, SOD, and CAT enzymes activity. However, the exogenous growth regulators reduced the negative effect for each of Na+, H2O2, and MDA under the salinity stress.